Mountain Observatories: Status and Prospects for Enhancing and Connecting a Global Community - Shahgedanova, Maria (2021)
Mountainous regions are globally important, in part because they support large populations and are biodiverse. They are also characterized by enhanced vulnerability to anthropogenic pressures and sensitivity to climate change. This importance necessitates the development of a global reference network of long-term environmental and socioeconomic monitoring-mountain observatories. At present, monitoring is limited and unevenly distributed across mountain regions globally. Existing thematic networks do not fully support the generation of multidisciplinary knowledge required to inform decisions, enact drivers of sustainable development, and safeguard against losses. In this paper, the Mountain Observatories Working Group, established by the Mountain Research Initiative (MRI) Science Leadership Council, identifies geographical and thematic gaps as well as recent advances in monitoring of relevant biophysical and socioeconomic variables in the mountains. We propose principles and ways of connecting existing initiatives, supporting emerging areas, and developing new mountain observatory networks regionally and, eventually, globally. Particularly in the data-poor regions, we aspire to build a community of researchers and practitioners in collaboration with the Global Network on Observations and Information in Mountain Environments, Group on Earth Observations (GEO) Mountains, a GEO Work Programme Initiative.